Design and psychometric evaluation of the Emergency Medical Services Safe Care Scale (EMSSCS): a mixed-method study - Fateme Mohammadi; Rasoul Salimi; Mohammadreza Shokouhi; Salman Khazaei; Mostafa Bijani (BMC Emergency Medicine)
Abstract Background Providing safe care by emergency medical services (EMS) personnel at the stressful scene of an incident is one of the most crucial factors influencing the preservation and enhancement of patient health. However, culture, attitudes, and social norms can influence the provision of care at the scene of an accident. Consequently, evaluating safe care practices at incident scenes is imperative and necessitates a specialized assessment tool. Presently, there is a lack of reliable and valid instruments for measuring safe care practices among EMS personnel. Therefore, this study was designed and conducted to develop and psychometrically evaluate the Emergency Medical Services Safe Care Scale (EMSSCS). Methods This investigation employed a mixed-methods design with a sequential exploratory approach, conducted from January 2024 onwards across the southwestern, western, and southeastern regions of Iran. The study was bifurcated into two distinct phases. In the initial phase, a conventional content analysis method was employed to scrutinize the narratives elicited from 41 EMS personnel. In the subsequent phase, the instrument’s validity and reliability were rigorously assessed. Results Safe care provided by EMS personnel was defined as the management of the incident scene, efficient clinical skills, and effective interaction aimed at delivering principled and safe patient care. Subsequently, based on the derived conceptual framework, a safe care instrument was designed with 44 items across three dimensions. During the qualitative and quantitative content validity 11 items, and face validity 3 items were deleted. Exploratory and confirmatory validity of this scale was approved in three dimensions: “incident scene management” (12 items), “efficient clinical skills” (10 items), and “effective interaction” (8 items). The scale’s reliability was reported at 0.95 using Cronbach’s alpha method. Conclusion The Emergency Medical Services Safe Care Scale (EMSSCS), demonstrated acceptable psychometric properties. Consequently, senior managers in pre-hospital emergency services can utilize this instrument to evaluate safe care practices among pre-hospital emergency medical technicians. They can identify the most appropriate strategies, including educational interventions, to enhance safe care provision at incident scenes when necessary. Clinical trial number Not applicable.